Globalisation and the Gender Earnings Gap : Evidence from Sri Lanka and Cambodia - Robertson, Raymond; Lopez-Acevedo, Gladys; Savchenko, Yevgeniya (Taylor and Francis, 2020)
Using household and labor force surveys from Cambodia and Sri Lanka, we find large positive wage premiums and a closing of the male-female wage gap during the Multi-Fiber Arrangement (MFA) period, but smaller premiums and a widening wage gap after the end of the MFA. Our results suggest that apparel exports continued to benefit women in developing countries post-MFA but women – both in and out of the apparel industry – are susceptible to changes in global apparel prices.